STUDY OF PSYCHOLOGICAL HEALTH OF EDUCATIONAL LEADERS (Scientific journal of the Fergana State University, 2024)
This annotation provides a concise examination of research on the psychological health of leaders in education. It delves into stressors faced by educational leaders, their coping mechanisms, and the impact on organizational dynamics. The connection between leaders’ well-being and their effectiveness is highlighted, alongside interventions and support systems aimed at bolstering mental health. Understanding and addressing the psychological health of educational leaders is pivotal for fostering a conducive work environment and optimizing organizational outcomes. Understanding managerial personality requires blending scientific and historical approaches. Scientific frameworks like the Big Five Traits and transformational leadership highlight key competencies. Historical analysis contextualizes these traits within societal and organizational contexts. Integrating both offers a comprehensive understanding, aiding selection processes and leadership development. This synthesis fosters adaptability and resilience, essential in today’s dynamic organizational landscape.